Distribusi Spasial Intensitas Penggunaan Lahan Tahun 2000 dan 2020 di Provinsi Gorontalo - Rakhmat Jaya Lahay; Nurdin Mohamad (Geosfera: Jurnal Penelitian Geografi, 2025)
The agropolitan policy implemented by the regional government in 2002 has driven changes in land use functions in Gorontalo Province. However, changes in land use intensity in Gorontalo Province have not been widely studied. This study aims to detect the spatial distribution of land use intensity from 2000 to 2020 in Gorontalo Province. A combination of Google Earth Engine and QGIS was chosen as the primary tools to detect the spatial distribution of land use intensity between 2000 and 2023 using the Global Land Cover and Land Use Change dataset. In general, the experimental results show that the area of land with medium-high and high land use intensity has increased significantly over the past two decades. This increase reflects the expansion of agricultural areas through the agropolitan program development activities by the provincial government since 2002. Thus, the use of the land use intensity index algorithm can provide information on landscape changes due to human activities. These findings are expected to serve as a reference in allocating land for future agricultural development purposes in Gorontalo Province.